2019
DOI: 10.1029/2018jc014700
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Atlantic and Pacific Bjerknes Feedbacks: Seasonality, Symmetry, and Stationarity

Abstract: The Bjerknes feedback is the dominant positive feedback in the equatorial ocean basins. To examine the seasonality, symmetry, and stationarity of the Pacific and Atlantic Bjerknes feedbacks we decompose them into three feedback elements that relate thermocline depth, sea surface temperature, and western basin wind stress variability to each other. We partition feedback elements into composites associated with positive or negative anomalies. Using robust regression, we diagnose the strength of each composite. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…Nnamchi et al (2015) showed that thermodynamic forcing by stochastic atmospheric perturbations can explain a significant amount of the observed SST variability in the equatorial Atlantic. Yet, recent studies assessing the relative importance of dynamic versus thermodynamic 1 3 processes conclude that the dynamic and in particular the Bjerknes feedback is a main driver for the Atlantic zonal mode (Jouanno et al 2017;Dippe et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nnamchi et al (2015) showed that thermodynamic forcing by stochastic atmospheric perturbations can explain a significant amount of the observed SST variability in the equatorial Atlantic. Yet, recent studies assessing the relative importance of dynamic versus thermodynamic 1 3 processes conclude that the dynamic and in particular the Bjerknes feedback is a main driver for the Atlantic zonal mode (Jouanno et al 2017;Dippe et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The ocean responds to the westerly wind stress anomaly by deepening the thermocline (Fig. 1e ) and thus increasing the heat content in the eastern equatorial Atlantic, which leads to warmer SSTs in this region 1 5 , 11 , 34 . However, the SST anomalies in the east do not drive a strong atmospheric response along the equator due to a lack of diabatic heating after June.…”
Section: Resultsmentioning
confidence: 99%
“…Such a picture is in part inconsistent with the Bjerknes-feedback loop, which does involve a strong feedback from the ocean to the atmosphere in the form of SST-forced atmospheric variability, as observed over the equatorial Pacific 12 , 13 and shown here in a companion analysis. This difference in ocean-atmosphere interaction between the Atlantic Niños and the Pacific El Niños may explain why SST variability is weaker 1 , 2 , 5 , 34 and SST predictability lower 44 , 45 in the equatorial Atlantic relative to that in the equatorial Pacific. These findings raise questions about the applicability of the standard Bjerknes-feedback loop as the major explanation for the mechanism underlying the Atlantic Niño.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics underlying the Atlantic Zonal Mode is in parts similar to that of the Pacific El Niño (Ding et al, 2010), so that the Bjerknes Feedback (Bjerknes, 1969) observed in the Tropical Pacific is also present in the Tropical Atlantic (Keenlyside and Latif, 2007). In its positive phase, anomalous warming in the eastern Atlantic coupled with weaker trade winds is associated with anomalous eastward currents bringing warmer waters from the west as well as weaker upwelling in the eastern equatorial region and deeper thermocline, which combined act to enhance the initial positive anomaly, closing the feedback cycle (Bjerknes, 1969;Chang et al, 2006;Keenlyside and Latif, 2007;Deppenmeier et al, 2016;Dippe et al, 2019;Silva et al, 2021). The opposite happens in its negative phase.…”
Section: Introductionmentioning
confidence: 92%